A Felvidék határait kijelölő vasutak - Majdán, János (Közép-Európai Közlemények, 2011)
The role of railways, played in modernization, can be seen in every European country, at the beginning as a result of constructional works of private companies and later, as a result of the construction of state owned companies. In Hungary both conceptions had their devotees. Now while speaking about upper part of Hungary we mean today’s Slovakia, but earlier this notion was used in a narrower sense. The Southern part of the region has no clearly defined geographic and ethnic borders, so among other factors, the railways may also help to give an exact definition concerning Upper Hungary. Taking into consideration the long first-class railways, it is possible to mark out two types of Southern borders: on the one hand the wider border is the main line which runs on the Little Plain, i.e. Wien–Érsekújvár–Pest, and the line running from the Hungarian capital to Miskolc, and through Miskolc to Sátoraljaújhely and to the Uzhok Pass. On the other hand it is situated west from the Hungarian capital, while in the east the valleys of Ipoly–Sajó–Hernád indicate the Southern border of Upper Hungary, considering railways. The smaller border is closer to ethnic borders.